Poxvirus MVA Expressing SARS-CoV-2 S Protein Induces Robust Immunity and Protects Rhesus Macaques From SARS-CoV-2 - Mooij, Petra; García-Arriaza, Juan; Pérez, Patricia; Lázaro-Frías, Adrian; Verstrepen, Babs E.; Böszörményi, Kinga P.; Mortier, Daniella; Fagrouch, Zahra; Kiemenyi-Kayere, Gwendoline; Niphuis, Henk; Acar, Roja Fidel; Meijer, Lisette; et al. (Frontiers in Immunology, 2022)
Novel safe, immunogenic and effective vaccines are needed to control COVID-19 pandemic, caused by SARS-CoV-2. Here, we describe the safety, robust immunogenicity and potent efficacy elicited in rhesus macaques by a modified vaccinia virus Ankara (MVA) vector expressing a full-length SARS-CoV-2 spike (S) protein (MVA-S). MVA-S vaccination was well tolerated and induced S and receptor binding domain (RBD)-binding IgG antibodies and neutralizing antibodies against SARS-CoV-2 and several variants of concern. S-specific IFNγ, but not IL-4, -producing cells were also elicited. After SARS-CoV-2 challenge, vaccinated animals showed a significant strong reduction of virus loads in bronchoalveolar lavages (BAL) and decreased levels in throat and nasal mucosa. Remarkably, MVA-S also protected macaques from fever and infection-induced cytokine storm. Computed tomography and histological examination of the lungs showed reduced lung pathology in MVA-S vaccinated animals. These findings favor the use of MVA-S as a potential vaccine for SARS-CoV-2 in clinical trials.